È ancora praticabile il metodo di Jaeger? - Bertelli, Lucio (ΠΗΓΗ/FONS, 2016)
Werner Jaeger claims to himself the discovery of an “organic evolution” within the works of Aristotle, publishing the results of his research in a famous monograph dated 1923. The comparison of the reviews and studies that followed on this epochal book shows not complete originality of Jaeger positions and, more important, how problematic result some of its basic principles.
Keywords: Aristotle’s Politics; Werner Jaeger; “Organic Evolution”; Method